Simultaneous removal of Cr(III) from high contaminated soil and recovery of lactic acid from the spent solution. (15th August 2020) - Andreozzi, R.; Fabbricino, M.; Ferraro, A.; Lerza, S.; Marotta, R.; Pirozzi, F.; Race, M.
Abstract: It is proposed a closed-loop treatment cycle for Cr(III) removal from contaminated soils (2080 mg/kg). The treatment includes the use of lactic acid as washing agent, and the recovery of both Cr(II) and lactic acid from the spent solution. Results indicate that Cr(III) removal efficiency can be very high, passing 70% in all tested operative conditions. The metal forms strong complexes with lactic acid, and therefore cannot be eliminated through direct precipitation simply increasing the pH value. Therefore, lactic acid is preliminarily extracted from the solution using n-butanol at very acidic pH. The obtained extraction degree is generally high, varying between 0.5 and 1 according to the amount of used n-butanol solution. After lactic acid extraction, almost 100% of chromium can be recovered through precipitation in alkaline conditions. Lactic acid, in turns, can be purified and reused for a new washing treatment, separating it from n-butanol solution through water extraction. The extraction efficiency is once more satisfying (around 0.5), and not dependent on the operative pH. Graphical abstract: Image 1 Highlights: Lactic acid can be successfully used for Cr(III) removal from contaminated soils. Complexes formed between lactic acid and Cr(III) are very stable. Lactic acid can be recovered from soil-washing spent solution with high efficiency. Lactic acid purity after liquid:liquid extraction with n-butanol is very high. n-butanol used for lactic acid extraction can be recovered with high efficiency.